Faecal analysis suggests generalist diets in three species of Western Cape cordylids - Clusella-Trullas, S.; Botes, A. (African zoology, 2008)
Climate has been proposed as an explanation for the present-day distribution of closely-related melanistic and non-melanistic cordylid species in the southwestern Cape of South Africa. However, diet may also contribute towards shaping geographic distributions. We present preliminary data on diet composition based on analyses of faecal pellets of Cordylus cordylus (non-melanistic), C. niger (melanistic) and C. oelofseni (melanistic). Coleoptera were the most common prey ingested both in summer and early spring for all species, followed by Hymenoptera for all species in summer. The overlap in other arthropod taxa ingested was low across species and seasons, suggesting an opportunistic component to their foraging behaviour. We distinguished plant matter in faecal samples of all species in all seasons, reflecting either voluntary or accidental ingestion. The results of this study suggest that the generalist diets of these cordylid species should not constrain their distributions despite the common preference for coleopterans.